(untitled) (Journal of the College of Basic Education, 2022)
Field experiment carried out in the fields of the Department of Plant Protection, College of Agriculture, University of Baghdad, in 2008 agricultural season. The results showed significant difference in the watermelon varieties, the location variety showed resistance to wilt disease under field conditions. The crimson variety that treated with Sulfur 82g/plant around the region of root and crown showed lower rate of infection was 0.00% .All treatment that treated with sulfur showed significant result fore the three varieties Charleston, Crimson and charley the incidence was 24.6,8.3% and 0,8.3% and 35,50% for percentage and intensity of infection respectively compared with control treatments. The location variety showed negative effect to sulfur treatment. Affected the treatment of sulfur + Carbendazin 50% (20g/D) fungicide negative effect in Charleston and local variety in percentage and intensity,